2019
DOI: 10.1111/dme.13977
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone deficiency in men with Type 2 diabetes: pathophysiology and treatment

Abstract: Epidemiological studies consistently demonstrate that lowered serum testosterone is not only common in men with established Type 2 diabetes, but also predicts future diabetic risks and increased mortality. Preclinical studies report plausible mechanisms by which low testosterone could mediate dysglycaemia. Exogenous testosterone treatment consistently reduces fat mass, increases muscle mass and improves insulin resistance in some studies, but the majority of currently available randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 85 publications
(126 reference statements)
0
45
0
1
Order By: Relevance
“…Those indicated that the effect of vitamin D on the serum testosterone levels may be opposed between males and females. Moreover, several observational studies and randomized trials have proposed that low serum testosterone status were correlated with an increased risk of IFG and T2DM in males and the opposite in females [22,[53][54][55][56]. It seems plausible that males with higher vitamin D levels likely have higher testosterone levels, which decrease the risk of IFG and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Those indicated that the effect of vitamin D on the serum testosterone levels may be opposed between males and females. Moreover, several observational studies and randomized trials have proposed that low serum testosterone status were correlated with an increased risk of IFG and T2DM in males and the opposite in females [22,[53][54][55][56]. It seems plausible that males with higher vitamin D levels likely have higher testosterone levels, which decrease the risk of IFG and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observational studies, reviewed in detail recently (Grossmann, 2018;Gianatti & Grossmann, 2019), have reported that diabesity (including the metabolic syndrome) is associated with a more rapid decline in testosterone, suggesting a bidirectional association (see below). Consistent with earlier work, in a recent prospective study of 141 younger (mean age 43 years) mostly insulin resistant men, insulin resistance (measured using an octreotide-based pancreatic suppression test) predicted hypogonadism (defined as a total testosterone < 10.4 nmol/L) somewhat more strongly (risk ratio = 2.2) than hypogonadism predicted insulin resistance (risk ratio = 1.3) (p = 0.03) (Contreras et al, 2018).…”
Section: Testosterone Thresholdmentioning
confidence: 99%
“…RCTs in men with T2DM and/or the metabolic syndrome published before 2016 have been extensively reviewed elsewhere (Dhindsa et al ., 2018; Grossmann, 2018; Rastrelli et al ., 2018; Gianatti & Grossmann, 2019). Overall, findings suggested that testosterone treatment consistently and modestly increases lean mass (by about 2 kg), decreases fat mass (by about 2 kg), and modestly improves insulin resistance in most but not all studies.…”
Section: Metabolic Impact Of Testosterone Treatment In Clinical Trialsmentioning
confidence: 99%
“…A 20-year-old man presented to a specialist for endocrinology and andrology with complaints of fatigue, dry mouth, and ED. The patient showed class III obesity with a body [18][19][20][21]. Recent study showed that long-term TTh may prevent prediabetes progression to T2D in men with hypogonadism, improve glycemic and lipid metabolism [22].…”
Section: Case Presentationmentioning
confidence: 98%